Cellular and humoral immunity in children with asthma - Dudnyk, V. M.; Fedchushen, A. P.; Khromykh, K. V. (Journal of Education, Health and Sport, 2017)
Asthma – is a chronic inflammatory disease of the airways, which most researchers attribute to allergic diseases which are based on immunological mechanisms, essentially even at present the subject of numerous studies. The aim of our study was to determine the cellular and humoral immunity in children with various forms of asthma. We have comprehensively examined 200 children with asthma aged 6 to 17 years. Found that state humoral and cellular immunity in patients with asthma differs depending on the form of the disease, such as serum IgA was at 24.68% higher at nonatopic asthma compared with atopic its form. Phagocytic index in children with asthma in nonatopic 2.92 times higher than in atopic asthma, indicating the presence of an infectious factor. Marked changes in cellular and humoral immunity depending on the content of 25 (OH) D3 and cathelitcidin LL-37. Thus, the value of IgA was 1.75 times higher in patients with the optimal content of 25 (OH) D3 in the serum, unlike the parameters in children with failure and deficiency of this vitamin. Found that in children with asthma containing cathelitcidin LL-37 inthe serum of more than 51.9 pg / ml phagocytic index at 44.74% higher compared to patients in whom serum content cathelitcidin LL-37 was less than 17 55 pg / ml